2012
DOI: 10.1016/j.lungcan.2012.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of afatinib (BIBW 2992) in patients with lung adenocarcinoma with mutations in the kinase domain of HER2/neu

Abstract: Human epidermal growth factor receptor (HER)2/neu kinase domain mutations are found in approximately 1-4% of lung adenocarcinomas with a similar phenotype to tumors with epidermal growth factor receptor (EGFR) mutations. Afatinib is a potent irreversible ErbB family blocker. We determined the tumor genomic status of the EGFR and HER2 genes in non- or light smokers with lung adenocarcinoma in patients who were entered into an exploratory Phase II study with afatinib. Five patients with a non-smoking history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(163 citation statements)
references
References 19 publications
(20 reference statements)
5
154
0
4
Order By: Relevance
“…The mutant cells [28] and patients [31] exhibited exquisite sensitivity to the irreversible dual-specificity EGFR/ERBB2 kinase inhibitor BIBW2992, afatinib. Trastuzumab-besed therapies effective cases were previously reported [30]. However in our cohort, only one case had Hercep Test 1+.…”
Section: Page -03mentioning
confidence: 49%
See 1 more Smart Citation
“…The mutant cells [28] and patients [31] exhibited exquisite sensitivity to the irreversible dual-specificity EGFR/ERBB2 kinase inhibitor BIBW2992, afatinib. Trastuzumab-besed therapies effective cases were previously reported [30]. However in our cohort, only one case had Hercep Test 1+.…”
Section: Page -03mentioning
confidence: 49%
“…It has shown that the common erbB2 mutation, A775insYVMA, lead to oncogenic transformation in a cellular assay [23]. Because one co-existed case with erbB2 and Kras mutation was reported [30], we have also examined the Kras mutant cases. However, in our cohort, Kras and erbB2 mutations were exclusive.…”
Section: Page -03mentioning
confidence: 99%
“…Although anti-Her2 therapies are ineffective in HER2-amplified NSCLC [98,99] , HER2-mutant NSCLC has been shown to be responsive to trastuzumab plus chemotherapy, with an overall response rate of 50% and median PFS of 5.1 mo in one case series [96] . Afatinib, the ErbB family inhibitor approved for EGFR-mutant NSCLC as discussed earlier in this review, also has clinical activity against HER2-mutant NSCLC in a small case series [96,100] . As HER family members signal via the PI3K-AKT-mTOR cascade, recent attempts have been made to inhibit both HER2 and mTOR in HER2-driven cancers.…”
Section: Other "Actionable" Molecular Targetsmentioning
confidence: 96%
“…Several TKIs are being tested in HER2-dependent lung adenocarcinomas. A phase II trial of the EGFR/HER2 dual inhibitor afatinib showed responses in three of five pretreated patients with advanced NSCLC with prospectively identified HER2 mutations (35). The preliminary results from an ongoing phase II trial of dacomitinib, another oral pan-HER irreversible TKI, described three responses out of 18 evaluable patients with HER2-mutant NSCLC (NCT00818441) (8).…”
Section: Her2 Amplification and Insertionsmentioning
confidence: 99%